Does Implant Density Impact Three-Dimensional Deformity Correction in Adolescent Idiopathic Scoliosis with Lenke 1 and 2 Curves Treated by Posterior Spinal Fusion without Ponte Osteotomies? - Thamrong Lertudomphonwanit; Chirag A. Berry; Viral V. Jain; Peter F Sturm (Asian Spine Journal, 2022)
Study Design Retrospective cohort study. Purpose To determine whether implant density impact three-dimensional deformity correction in posterior spinal fusion (PSF) without Ponte osteotomies (POs) for patients with Lenke 1 and 2 adolescent idiopathic scoliosis (AIS). Overview of Literature Currently, the optimal pedicle screw (PS) density for flexible moderate-sized thoracic AIS curve correction is still controversial. There are limited data regarding the impact of implant density on three-dimensional correction in PSF without the use of PO for thoracic AIS surgery. Methods A database of patients with AIS with Lenke 1 and 2 curves treated with PSF without PO and instrumented with PSs and ≥2-year follow-up was reviewed. The preoperative, immediate, and final follow-up postoperative radiographs were analyzed. The correlation between PS density and the following factors were determined: major curve correction (MCC), correction index (CI; MCC/curve flexibility), kyphosis angle change, and rib index (RI) correction. Then, patients were divided into low-density (LD) and high-density (HD) groups according to mean PS density for the entire cohort (1.5 PS per level). Demographics and radiographic and clinical outcomes were compared between groups. Results The study included 99 patients with Lenke 1 and 23 patients with Lenke 2 AIS. The average MCC was 67.2%. There was no correlation between screw density and these parameters: MCC (r=0.10, p=0.26), CI (r=0.16, p=0.07), change in T2–T12 kyphosis angle (r=−0.13, p=0.14), and RI correction (r=−0.09, p=0.37). Demographic and preoperative radiographic parameters were similar between the LD and HD groups. At the latest follow-up, there were no differences between the two groups in regard to MCC, CI, change in T2–T12 kyphosis angle, RI correction, and Scoliosis Research Society-30 scores (all p>0.05). Conclusions This study revealed no significant correlation between screw density and curve correction in any planes. HD construct may not provide better deformity correction in patients with flexible and moderate thoracic AIS undergoing PSF without PO.